The Effects of Hedging, Leverage, Profitability, Liquidity, and Capital Intensity on Tax Aggressiveness Moderated by Company Size - Wijoyo, Amin; Imanuel, Steven; Goodwin, Bryan; Wiryajaya, Steven (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Tax aggressiveness in Indonesia’s energy sector is a critical issue as companies aim to reduce tax burdens while navigating regulatory constraints. This study examines how hedging, leverage, profitability, liquidity, and capital intensity affect tax aggressiveness, with company size as a moderating factor, in energy firms listed on the Indonesia Stock Exchange. The research analyzes 34 companies from 2021 to 2023, totaling 102 observations, using panel data regression with fixed and random effect models processed via statistical software. Findings show that leverage increases tax aggressiveness, while profitability reduces it, contrary to expectations, possibly due to tax shields and oversight. Hedging, liquidity, and capital intensity have no direct impact, likely due to low derivative use and regulatory limits. Company size strengthens the effects of leverage and capital intensity but not others. The model explains 77.2% of tax aggressiveness variance without moderation and 10.2% with it. These results highlight unique tax planning dynamics in the energy sector, offering insights for firms to balance debt and liquidity and for policymakers to target larger companies for compliance.